Civil society and political change in Asia : expanding and contracting democratic space - Alagappa, Muthiah (Stanford University Press, 2004)
"This book is the first comprehensive, systematic investigation of the connection between civil society and political change in Asia - change toward open, participatory, and accountable politics. Its findings suggest that the link between a vibrant civil society and democracy is indeterminate: Certain types of civil society organizations support democracy, but others have the potential to undermine it."--Jacket